Current insights on the genetics and mechanisms of MSX1-associated cleft palate - AC. Myo; R. Raju; J. O. Piña; P. Chattaraj; M. Furukawa (Frontiers in Dental Medicine, 2025)
Cleft palate, a common congenital anomaly, is characterized by a failure of the palatal shelves to fuse during embryogenesis, resulting in an opening between the oral and nasal cavities. This malformation not only affects facial aesthetics but also significantly impacts speech, feeding, and hearing, necessitating multidisciplinary care from birth through adulthood. The etiology of cleft palate is complex, involving both genetic and environmental factors. Among the numerous genes implicated, Msx1 plays a pivotal role in palatal development. As a transcription factor, Msx1 regulates mesenchymal cell proliferation and epithelial-mesenchymal interactions, processes crucial for proper palatal shelf elevation and fusion. Disruptions in Msx1 expression or function have been directly linked to cleft palate through both animal and human studies, highlighting its significance in palatogenesis. This review focuses on the role of Msx1 in cleft palate, providing a comprehensive overview of its functions and the molecular mechanisms through which it influences palatal development. We examine recent research findings, including studies on Msx1 mutations, signaling pathways, and gene-environment interactions, to elucidate the complex relationship between Msx1 and cleft palate. Moreover, advancing research could establish Msx1 as a fundamental target in the creation of innovative therapeutic strategies for craniofacial disorders. By synthesizing current knowledge, this review aims to provide a deeper understanding of Msx1's role in cleft palate and pave the way for future research and clinical advancements.